In vitro & in vivo evaluation of antiangiogenic potential of Docetaxel and Meloxicam – A drug repurposing approach - SAMEER K PANDA; ASHISH WADHWANI (International Journal of Pharma and Bio Sciences, 2018)
Angiogenesisis a physiological process where new vasculature is formed by a series of cascading steps - endothelial sprouting, endothelial cell migration, proliferation and tube formation. Tumors require vascular networking system for their nutrient supplement, which may encourage the growth of the tumor. The microtubule altering drug Docetaxel and COX-2 inhibitor Meloxicam is expected to have anti-angiogenic property. This study aims to evaluate the anti-angiogenesis activity of Docetaxel and Meloxicam using various angiogenesis models. The MTT assay was performed to find the IC50 value of both drugs on Vero and U-87 cell lines. The endothelial tube formation on U87 was performed by using 125µg/ml and 250µg/ml concentrations of the selected drugs. The Chorioallantoic Membrane Assay (CAM) setups were composed of a positive control (DMSO), negative control (Saline) Docetaxel (12.5µg, 25µg, 50µg) and Meloxicam (62.5µg, 125µg, 250µg). They were encapsulated into agarose discs and implanted. The in vivo aortic ring assay was performed in order to observe the in vivo effects of both the drugs. The IC50 values of Docetaxel and Meloxicam were found to be 367.28 ± 0.96 & 127.29 ± 1.22µg/ml and 387.63 ± 1.87 & 142.85 µg/ml in Vero and U87 respectively. Both the drugs, at a concentration of 125µg/ml, were found to be effective in inhibiting the endothelial tube formation and healthy vessel formation in aortic ring assay. Docetaxel at a concentration of 25µg/ml and Meloxicam at concentration of 125µg/ml inhibited vasculature in CAM model. The above observations indicated that Docetaxel and Meloxicam possess promising antiangiogenic potential and further in depth studies can be performed to confirm the use of Doxetaxel and Meloxicam as anti-angiogenesis drugs.